Influencing of thin protective coatings on natural frequencies of radial oscillations of claddings of fuel rods of nuclear reactors - Mazurenko, Yu.E.; Romashov, Yu.V.; Mamalis, A.G. (Вопросы атомной науки и техники, 2020)
The natural frequencies and the modes of the radial oscillations are computed by using the method of grids for the cylindrical claddings made with the thin protective coatings for the fuel rods of the nuclear reactors. It is received the values more than 150 kHz for first natural frequencies of the radial oscillations of the claddings of fuel rods of the WWER-1000 nuclear reactors. It is shown that the thin protective coatings lead to noticeable increasing of first natural oscillation frequency, but have negligible influencing on the second and higher natural frequencies as well as on the modes of the radial oscillations of the claddings of fuel rods.